Partnering for prosperity: small IT vendor partnership formation and the establishment of partner pools. Issue 2 (4th March 2021) - Findikoglu, N Melike; Ranganathan, Chandrasekaran; Watson-Manheim, Mary Beth
ABSTRACT: Small IT vendors increasingly establish intra-industry collaborative arrangements with other technology providers. Despite the criticality of this strategy, there is little research that provides insights into partnership formation. Our study attempts to close this gap.Building on resource dependency theory (RDT) and resource-based view (RBV), we posit that, depending on external market and internal resource considerations, small IT vendors either supplement or complement their IT resources and capabilities via partnerships. When seeking to expand the scope of their resource portfolio by accessing dissimilar resources, vendors are engage in complementary partnerships (goal: improving the scope of IT resources). However, if they seek to expand the scale of their portfolio, they engage in supplementary partnerships (goal: extending the scale of IT resources). Using a qualitative approach, we examine the partnership formation practices of seven small IT firms. We propose a conceptual framework with five constructs that illustrate dynamics underlying these IT service partnerships, i.e., External market considerations, Internal resource configurations, Partner considerations, Partnership exploration, and Partnership development. We find variations in partnership practices depending on the supplementary or complementary nature of resources being sought. We also find small IT vendors form and manage partner pools to mitigate risks associated with partnerships.